Interactions between clusters of self-interstitial atoms via a conservative climb in BCC–Fe. Issue 25 (2nd September 2018) - Hayakawa, Sho; Okita, Taira; Itakura, Mitsuhiro; Aichi, Masaatsu; Suzuki, Katsuyuki
ABSTRACT: We conduct kinetic Monte Carlo simulations for the conservative climb motion of a cluster of self-interstitial atoms (SIAs) towards another SIA cluster in BCC–Fe; the conservative climb velocity is inversely proportional to the fourth power of the distance between them, as per the prediction based on Einstein's equation. The size of the climbing cluster significantly affects its conservative climb velocity, while the size of the cluster that originates the stress field does not. The activation energy for the conservative climb is considerably greater than that derived in previous studies and strongly dependent on the climbing cluster size. The results presented in this study are the atomistic evaluation of the behaviour of SIA clusters through three-dimensional motion, which cannot be achieved using molecular dynamics techniques alone.